2015
DOI: 10.1128/jvi.02176-14
|View full text |Cite
|
Sign up to set email alerts
|

CD4+T Cell Help Is Dispensable for Protective CD8+T Cell Memory against Mousepox Virus following Vaccinia Virus Immunization

Abstract: It has been shown in various infection models that CD4؉ T cell help (T H ) is necessary for the conditioning, maintenance, and/or recall responses of memory CD8 ؉ T cells (CD8 M) . Yet, in the case of vaccinia virus (VACV), which constitutes the vaccine used to eradicate smallpox and is a candidate vector for other infectious diseases, the issue is controversial because different groups have shown either T H dependence or independence of CD8 M conditioning, maintenance, and/or recall response. In agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…This model is supported by our data, showing that NK cell-derived IFN-γ is necessary to prevent the earlier published capacity of VACV to downregulate MHC-II expression on macrophages [54][55][56]. Previous studies already indicated that T cells were major producers of the second IFN-γ wave after VACV infection and that the presence of IFN-γ expressing CD8 + T cells was of key relevance to control the infection [15,18,57]. Nevertheless, we found that Ncr1-specific reconstitution of the IFN-γ gene function was sufficient to confer activation of the myeloid cell compartment upon VACV infection and to control the infection.…”
Section: Discussionsupporting
confidence: 86%
“…This model is supported by our data, showing that NK cell-derived IFN-γ is necessary to prevent the earlier published capacity of VACV to downregulate MHC-II expression on macrophages [54][55][56]. Previous studies already indicated that T cells were major producers of the second IFN-γ wave after VACV infection and that the presence of IFN-γ expressing CD8 + T cells was of key relevance to control the infection [15,18,57]. Nevertheless, we found that Ncr1-specific reconstitution of the IFN-γ gene function was sufficient to confer activation of the myeloid cell compartment upon VACV infection and to control the infection.…”
Section: Discussionsupporting
confidence: 86%
“…Since primary virus infection was controlled by all genotypes ( Fig. 5D ), this suggests the possibility that the combination of a reduced CD8 + T-cell response with impaired CD4 + T-cells and antibody production during the acute response may explain virus control after primary infection even in the Cd4-cre;Parp2 f/f ;Parp1 −/− mice, as these three immune responses are each relevant to control VACV acute infection 39 40 .…”
Section: Resultsmentioning
confidence: 97%
“…As observed with primary CTL responses, memory CTL formation in certain circumstances can also be largely independent of CD4 + help, as observed after vesicular stomatitis virus (11) or ectromelia (mousepox) virus infection (12). Moreover, the extent of CD4 + T cell-dependence for the establishment of CTL memory can also vary for responses targeted to different peptides from the same immunogen (13).…”
mentioning
confidence: 94%